The solution of d x d y = 2 x y x 2 + y 2 + 1 satisfying y ( 1 ) = 0 is given by
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think it will be a hyperbola for all real values of c .
Set y ′ = 0 to arrive at x 2 + y 2 + 1 = 0 . Which is true for no pair of real x , y . We can discard the first two options with this since both have zero slope at some point. Consider the scalar function given by y ′ ( x , y ) = 2 x y x 2 + y 2 + 1 . And now consider y ′ ( 1 , y ) = y 1 + 2 y We notice that for positive "y" this function gives positives values, and the same thing happens for negative y. As y approaches 0, y' tends to infinity; which suggests that we're dealing with an hyperbola with one vertex at (0,1) (since at such point it has a vertical slope) and extending along the positive x-axis. Propose ( x / a ) 2 − ( y / b ) 2 = 1 . Plug it in the ode to obtain: b 2 − 1 = x 2 ( 1 − ( b / a ) 2 ) . Alude to the linear independence of polynomials to get that both a and b are +-1. Hence the desired solution.
Problem Loading...
Note Loading...
Set Loading...
Let us write the above DE as the following:
y' = (x^2 + y^2 + 1)/2xy;
or x*(2yy') = x^2 + y^2 + 1;
or x*(2yy') - y^2 = x^2 + 1.
If we now divide both sides by x^2, we arrive at:
[x*(2yy') - y^2] / x^2 = (x^2 + 1) / x^2;
or (y^2 / x)' = 1 + 1/x^2 (i).
Integrating both sides of (i) with respect to x gives: y^2 / x = x - 1/x + C, and the boundary condition y(1) = 0 yields C = 0. We ultimately end up with the equation:
y^2 / x = x - 1/x => y^2 = x^2 - 1 => x^2 - y^2 = 1
or a hyperbola.